1992
DOI: 10.1007/bf01948004
|View full text |Cite
|
Sign up to set email alerts
|

Phosphocreatine and ATP concentrations increase during flow-stimulated metabolism in a non-contracting muscle

Abstract: The gracilis muscle was excised from cold-acclimated rats, placed in vitro, and simultaneously perfused via its artery by high pO2 medium and superfused by low pO2 medium. With a doubling of the perfusion rate (from 50 to 100 microliters/min) phosphocreatine and ATP increased by 39% and 44%, respectively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
4
0

Year Published

1996
1996
2006
2006

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 7 publications
2
4
0
Order By: Relevance
“…The data from this study confirm the stimulatory effect of perfusion flow rate on oxygen consumption in a muscle with open microcirculation, perfused and superfused in vitro (Chinet & Mejsnar, 1989;Mejsnar et al 1992;Stefl et al 1994). On a macroscopic scale the delivery of oxygen was sufficiently high to cover oxidative metabolism, even under a low perfusion rate, so that the availability of oxygen is not the cause of the flow dependency of the muscle oxygen consumption.…”
Section: Discussionsupporting
confidence: 82%
“…The data from this study confirm the stimulatory effect of perfusion flow rate on oxygen consumption in a muscle with open microcirculation, perfused and superfused in vitro (Chinet & Mejsnar, 1989;Mejsnar et al 1992;Stefl et al 1994). On a macroscopic scale the delivery of oxygen was sufficiently high to cover oxidative metabolism, even under a low perfusion rate, so that the availability of oxygen is not the cause of the flow dependency of the muscle oxygen consumption.…”
Section: Discussionsupporting
confidence: 82%
“…Group 2: after 40 min recovery period with a perfusion flow rate of 0·054 ml min¢, the perfusion flow rate was increased to 0·100 ml min¢ for the next 60 min; n = 7. Controls: intact muscles of anaesthetized rats freezeclamped in situ; n = 10. discussion The data from this study confirm the stimulatory effect of perfusion flow rate on oxygen consumption in a muscle with open microcirculation, perfused and superfused in vitro (Chinet & Mejsnar, 1989;Mejsnar et al 1992;Stefl et al 1994). On a macroscopic scale the delivery of oxygen was sufficiently high to cover oxidative metabolism, even under a low perfusion rate, so that the availability of oxygen is not the cause of the flow dependency of the muscle oxygen consumption.…”
Section: Proportions Of Anaerobic and Aerobic Atp Synthesis Ratessupporting
confidence: 82%
“…The authors found that the energy fluxes measured by indirect and direct calorimetry differ, the former being higher in the range of perfusion rates from 50 to 150 ìl min¢ than the latter. This finding was further reinforced by the measurements of the increase in tissue levels of ATP and phosphocreatine (PCr) with 31 Pnuclear magnetic resonance spectroscopy (Mejsnar et al 1992) and by thermodynamic implications of the data (Mejsnar, 1991).…”
mentioning
confidence: 93%
“…It would a tabolism in cold-exposed rats [32]. To further examine priori appear more reasonable to expect the opposite the sensitivity of creatine compounds and adenine nuresult based on the basal metabolic rates.…”
Section: Discussionmentioning
confidence: 98%